Strategi Praktis Quality dan Quantity Check pada Sistem Pergudangan Produk Migas - Rendy Bagus Pratama; Yunanik Yunanik; Kushariyadi Kushariyadi; Dwi Nurma Heitasari; Ibnu Lukman Pratama; Nano Koes Ardhiyanto (PELITA NUSA TENGGARA, 2026)
The presence of oil and gas (oil and gas) storage facilities near residential areas often raises public concerns regarding potential hazards and environmental impacts. This Community Service (PkM) activity aims to educate residents in Cepu Regency about the importance of Quality and Quantity (Q&Q) processes and the implementation of Occupational Safety, Health, and Environment (K3) standards in oil and gas terminal storage facilities. The activity included interactive presentations using comprehensive infographics, discussions, and live Q&A sessions facilitated by the PkM team from PEM Akamigas. This visual and dialogic approach was used to simplify the understanding of technical oil and gas operational terminology for the general public. The results of this outreach activity demonstrated a significant increase in public literacy and understanding. Residents who were previously skeptical or anxious now understand that strict Quality Control (QC) processes prevent product contamination, while Quantity Measurement (QT) ensures fair energy distribution. Furthermore, the public became aware that the implementation of disciplined OHS procedures—such as fire extinguisher operation, early detection, and evacuation routes—was professionally designed solely to protect residents' safety and prevent environmental pollution. In conclusion, this community service activity, implemented in 2025, succeeded in building positive perceptions and a sense of security within the community. This activity effectively transformed concerns into trust in the operational standards of the oil and gas storage industry, while emphasizing the importance of transparent communication among industry, scientists, and the public to support safe and sustainable energy stability.